Resource recovery and zero waste management option of slaughter house waste in Khulna city corporation of Bangladesh (Journal of the Bangladesh Agricultural University, 2010)
Presently the slaughter houses of khulna city corporation (KCC) area in Bangladesh are being used in such a way that the wastes come from these are polluting the surrounding environment such as river water, solid surface, air etc. In this circumstance, the research analyzed the management options of this slaughter house wastes and determines how this process would be suitably managed through the community participation. To fulfill the above mentioned objective, the research work was conducted through the questionnaire survey, direct observation, face-to-face interview along with the random sample collection and relevant measures of different factors. The research finding reveals that the total quantity of waste produced from these slaughter houses was 2888.45 tonnes/year. The management of this volume of waste was found as unsatisfactory by the most of the stakeholder groups due to fail of the conservation of public health and ecosystem of the local community. However, the analysis of the research data and other relevant information suggest that the potential management system such as a zero waste management of the wastes of slaughter houses in Khulna City Corporation area is possible to implement for more environmentally friendly development of the society which have the potential to resource reuse (waste-to-energy recovery) and others. Finally, the research recommended three separate designs of the conventional biomethanation plant and a potential biogas production model for these slaughter houses. Keywords: Slaughter house; Biomethanation; Zero waste management; Energy recovery; Khulna city corporation DOI: 10.3329/jbau.v7i2.4742 J. Bangladesh Agril. Univ. 7(2): 321-327, 2009